Examining the Impact of Virtual Tour Service Quality on Visitor Satisfaction in Digital Museum Environments - Chairul Rizal; Erni Marlina Saari (Ali Institute or Research and Publication, 2026)
Research on virtual museums has expanded globally; however, empirical evidence from Indonesian digital cultural heritage institutions remains limited, particularly regarding how service quality shapes visitor satisfaction in fully virtual environments. Addressing this gap, this study investigates the influence of virtual tour service quality on visitor satisfaction at the Museum Kebangkitan Nasional, Indonesia, and examines the applicability of established service quality frameworks within a digital heritage context. Using a quantitative research design, data were collected through a structured survey from 97 users of the museum’s virtual tour platform. Measurement instruments were adapted from SERVQUAL and e-SERVQUAL models, incorporating digital-specific dimensions such as interactivity, system usability, interface aesthetics, and accessibility. Data analysis employed descriptive statistics, correlation analysis, and multiple regression techniques. The results reveal that virtual tour service quality has a significant positive effect on visitor satisfaction, explaining 41.6% of the variance, with respondents reporting high levels of perceived service quality and overall satisfaction. These findings demonstrate the novelty of extending traditional service quality models to virtual museum environments, where technological performance and user interface design emerge as critical experiential determinants. Theoretically, the study contributes to service quality and digital heritage literature by validating hybrid service quality constructs in a virtual cultural setting. Practically, it provides actionable insights for museum managers and cultural institutions in Indonesia to enhance digital engagement through user-centered design, platform reliability, and continuous technological innovation.